Visual Representations of Abandoned Industrial Spaces in Tourist Photos - Olga Vyacheslavovna Sergeeva; Elena Vladimirovna Nedoseka (Интеракция. Интервью. Интерпретация)
A few decades ago, an enthusiastic researcher would have found relatively few data to analyze, looking for such information about the ruins of modernity as the structural consequences caused by rapid cycles of industrialization and desolation, development and depopulation, conflict and reconciliation. However, conducting the same search today reveals an extraordinary increase in academic and public interest in the ruins of the recent past and the associated abandoned places. The authors of this article join in the discussion and explore the images of deindustrialization posted and distributed in the online communities among abandoned sites enthusiasts. The aim of the research is to form an idea of “everyday life policy” about the abandoned industrial facilities popularized by amateur photographers. “Everyday life policy” is expressed through the signifying and conceptualizing the abandoned and ruined places when putting them in a close-up. The authors rely on the ideas of the architect and historian I. de Sola-Morales, who calls the places left by people “terrain vague”. Photographic images of the terrain vague spaces play an important role in conceptualizing them. In order to understand what meanings exactly shaped the public policy, the authors use the ethnographic method of immersion in the online VKontakte/Telegram communities of abandoned sites enthusiasts to discover the recurring iconographic elements of the derelict places. Deindustrialization in photographs is reflected through 1) loss of human; 2) violence of vegetation or nature agency; 3) artifacts and texts of the past or material objects agency. The authors discuss the similarities of the images taken by amateur photographers and those media clich?s found in popular movies and video games. Photographs are a way of explaining space and spatial experience. Furthermore, like any other work of art, a photo conveys not only and not so much the actual characteristics of the depicted objects, thanks to which we can form an idea about them (in this case, about space), but also effects and experiences. Thus, a photograph becomes a tool that helps us form value judgments about the places we have seen.